In vivo visualization of mesoscopic anatomy of healthy and pathological lymph nodes using 7T MRI: a feasibility study - Freitag, Martin T.; Breithaupt, Mathies; Berger, Moritz C.; Umathum, Reiner; Hassel, Jessica C.; Ladd, Mark E.; Schlemmer, Heinz-Peter; Stieltjes, Bram (Journal of magnetic resonance imaging, 2015)
Purpose To evaluate whether inguinal lymph nodes (LNs) may be visualized in vivo using 7T magnetic resonance imaging (MRI) at high spatial resolution. Materials and Methods Twelve healthy controls and six patients with LN metastasis of melanoma were included. Examinations were performed using a 7T MRI and a transmit/receive loop coil. The protocol included a B0-map, B1-map, and T1-weighted-3D-fast low-angle shot (FLASH), T1w-Dixon-volumetric interpolated breath-hold examination (VIBE) and T2w sequences lasting 34.4 ± 0.5 minutes. Signal- and contrast-to-noise of LNs, artery, muscle, and fat were quantified in controls. Metastatic features of LNs (hypervascularization, lymph vessels, fat hilus sign, tumor bulk, number of metastases, and size) were classified in patients. Results Mesoscopic LN architecture such as central blood vessels and peripheral lymph vessels were observed in healthy controls with 0.5 mm3 isotropic resolution for T1w and 0.2 × 0.2 × 2 mm3 for T2w sequences. Mean signal-to-noise using 3D FLASH, Dixon VIBE and T2 TSE of healthy LN (27.2 ± 7.5, 35.3 ± 11.9, 31.7 ± 11.1), muscle (17.6 ± 4.6, 31.5 ± 9.3, 7.3 ± 5.4), artery (37.7 ± 5.9, 42.7 ± 19.7, 3.7 ± 3.9), and saturated fat (3.7 ± 0.9, 5.4 ± 1.9, 9.3 ± 5.2) and mean contrast-to-noise LN/fat (24.4 ± 6.7, 39.6 ± 11.1, 23.3 ± 6.1) were adequate. In patients, multiple signs of metastasis could be clearly visualized. Conclusion We present a protocol with which inguinal LNs and their mesoscopic anatomy may be visualized in vivo using 7T MRI. J. Magn. Reson. Imaging 2015;41:1405-1412. © 2014 Wiley Periodicals, Inc.
First published: 26 June 2014
Gesehen am 24.06.2020